New advances in the history of archaeology : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France). - Beaune, Sophie A. de,; Guidi, Alessandro, 1952-; Moro Abadía, Óscar,; Tarantini, Massimo, (UISPP proceedings series ;, 2021)
This volume presents papers from three sessions organised by the History of Archaeology Scientific Commission at the 18th UISPP World Congress (Paris, June 2018) considering the development of stratigraphical methods in archaeology in many European countries, and interdisciplinary perspectives on the history of archaeology.